Validation of the Malay version of impact of event scale-revised (IES-R) among flood disaster victims in Kelantan - Halim, Ahmad Shahril Ab. (2017)
Background: Post-traumatic stress disorder (PTSD) may result from exposure to extreme psychological stress post disaster and the Impact of Event Scale-Revised (IES-R) was probably the most widely used tool used for its measurement. Nevertheless, there is lack of evidence on proper validation of this instruments used in the Malaysian context. The objective of this study was to validate the Malay version of Impact of Event Scale-Revised (IES-R). Methods: A cross-sectional study, involving 168 participants who were involved in flood disaster in the Kuala Krai district, was conducted from April 2015 to June 2015. Back to back translation, content validity and face validity processes were conducted by a group of expert, followed by pilot study. The final version of the questionnaire then was used for the validation study. The data analyses involve assessment of construct validity by confirmatory factor analysis and composite reliability by Raykov‟s rho. Results: Our final model of IES-R (Malay) consists of 2 factors with 19 items, as compared to original version with 3 factors with 22 items. Our finding showed the final model has good model fit (CFI = 0.933, TLI = 0.923, RMSEA = 0.056, SRMR = 0.058) and composite reliability (Psychological = 0.89, Behavioural = 0.83). Conclusion: The study showed that the two-factor model with 19 items of the Malay version